Komposisi dan Struktur Komunitas Karang (Scleractinia) di Ekosistem Terumbu Karang di Perairan Pantai Nirwana Padang - Vany Helsa Anwar; Indra Junaidi Zakaria; Afrizal S (Jurnal Biologi Universitas Andalas, 2014)
A study on the composition and community structure of Scleractinia in coral reef ecosystem at coastal region Taman Nirwana Padang have been done from April - July 2013. This study was to know the competition and community structure of Scleractinia at coastal region Taman Nirwana Padang. The research was conducted by "Line Intercept Transect" and "Purposive Sampling" in two zones: Tourism zone and Mangrove zone and depth are 2-7 meters. Each zones have eight transects and each transect length of 25 meters. There are 50 coral species belong to 12 family at Nirwana beach. The highest relative density of coral species are A. palifera (RD 6.56%), Galaxea fasicularis (RD 5, 96%), Pocillopora damicornis (RD 5.79%), Goniopora pandoraensis (RD 5.27%), Goniastrea pectinata (RD 4.92%), P. lobata (RD 4.58%). Diversity index of coral species at coastal region Taman Nirwana is high (3.566). Diversity index of each zone are Tourism zone (3.533) and Mangrove zone (3.502). The equitabilities index are 0,907 (Tourism zone) and 0.909 (Mangrove zone). The composition of coral species at two zone at coastal region Taman Nirwana were in stable condition, and a similarity index is 95.8%. Keywords: Coral, composition, Community, Nirwana Beach